Breaking the Glass Ceiling: Germany and its obligation to equal leadership representation under CEDAW - Hagedorn, Katharina (Department of Public Law, 2024)
CEDAW guarantees equal rights for men and women. Its member states are obliged to implement those rights through policies and legislation, to enact the overall goal of social and structural change. CEDAW and its Committee have not made clear whether that includes a right to equal representation of women in senior and leadership positions. According to the World Economic Forum's Global Gender Gap Report, Germany is one of the leading countries in providing women with equal rights. However, they trail behind other European countries in their efforts of achieving equal representation in senior and leadership positions. My research therefore consists of two main questions: does CEDAW include a right to equal leadership representation? If so, is Germany fulfilling that obligation? The answer to those questions will provide a base for further research in that area. The identified shortcomings will be helpful in holding Germany's government accountable for its obligations under CEDAW as well as revealing areas of improvement. This research takes a legal approach, rather than an economic or sociological approach and uses desktop and literature research. I considered the principles of equality and the specific provisions within CEDAW to conclude that it does contain a right to equal leadership representation. Equally, I studied the legislation in Germany regarding women's quotas for management positions in Germany's biggest companies (First and Second Management Positions Act). I conclude that the Leadership Positions Act, being classified as a temporary special measure under CEDAW, is currently sufficient to fulfil the obligation to equal leadership representation. However, there is a need for constant re-evaluation and I recommend increasing the women's quota included in the Act from 30 Per cent to 40 Per cent.